The Role of Influencers on Young Consumer Behavior: A Systematic Review - Barrueta-Pinto, Mark (2025)
The systematic review approaches the role of influencers on young consumers. It provides clues about the consumption behavior of young people and the characteristics of influence. The methodology follows the PRISMA statement. The Scopus and Web of Science search yielded 432 articles from the last 5 years, and 29 were selected. The significant impact of influencers on young consumer behavior is highlighted, emphasizing the crucial role of social media and influencer marketing, especially influencer credibility. Key topics include the magnitude of influence on young people, the relationship between relationship strength and trust, and the perception of authenticity in collaborations with brands. Disclosure affects perception, highlighting the importance of trust and credibility in influencer marketing campaigns. Brands must carefully evaluate influencers to maintain audience trust in their publications. Future studies could evaluate whether the influence of influencers is long-term or studies with different cultural contexts or how this influence psychologically affects the mental health of young people.